Sri Lanka's response to prescribed drug misuse: is it enough? - Aruni Hapangama; K. A. L. A. Kuruppuarachchi (BJPsych International, 2023)
A wide range of medications are being misused by people the world over and Sri Lanka is no exception. Reasons for this misuse are manyfold. Regulatory bodies, prescribers, dispensers, as well as the general public, have significant roles to play in mitigating the misuse of prescribed medications and their harmful consequences.